Governanve im Zeitalter des Terrors: Der Fall Irak - Alnasseri, Sabah (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
The war in Iraq can neither be understood as a sectarian nor as a civil war, rather, it implicitly refers to internal struggles for power within the governing cliques and their opponents. The civil war artefact is presented by the occupier and the governing cliques in Iraq. The rational behind the construction is to further legitimize the occupation and the presence of an ever-increasing number of troops, on which the position of power of the governing cliques relies immensely. Rather than a civil war, what exists is a correlation of political power and economic interest between the Bush administration and the ruling cliques in Iraq in as much as both political agendas depend on the compliance of the other.